Vacuum preloading method for land reclamation using hydraulic filled slurry from the sea: A case study in coastal China. (15th March 2018) - Zhu, Wenlong; Yan, Jianming; Yu, Guoliang
Abstract: This study observed an engineering project, in which the vacuum preloading method incorporated with the vertical drain system was applied to the improvement of the dredged marine clay slurry as the fill as well as the in-situ soft ground for land reclamation. The site conditions, field instrumentation, construction process and partial requirements of the vacuum preloading project are described in this paper. Field monitoring data is presented and analyzed. After the vacuum preloading, the average degree of consolidation achieved was more than 88%, and the bearing capacity of the dredged marine clay slurry was improved from less than 4 kPa to be higher than 50 kPa. Specifications of construction techniques were detailed which would be useful and referenceable to engineers. Three empirical prediction methods for estimating the ultimate settling and consolidation degree are reviewed. Several key parameters and their optimal values in the formulae are discussed and suggested, respectively. Prediction results show that the Asaoka's method is the most preferable for predicting the settling of dredged marine clay slurries with high initial water content improved by vacuum preloading. Highlights: Construction processes and partial technique requirements of a successful vacuum preloading project are introduced. Specifications of construction techniques for consolidating the dredged marine clay slurry were detailed. Three empirical prediction methods for the prediction of ultimate settlement and consolidation degree are mainly discussed. Several key parameters and their optimal values in the formulas are discussed and suggested, respectively. The prediction accuracy using the exponential curve method and Asaoka's method are higher than the hyperbolic curve method. The Asaoka's method is the most preferable prediction method for dredged marine clay slurries applied by vacuum preloading.